Monaster Świętej Trójcy w Markowie pod Witebskiem = The Holy Trinity Orthodox Monastery at Markowo near Witebsk - Boberska, Marta; Boberski, Wojciech (2021)
A monograph study on the Orthodox Monastery of the Holy Trinity at Markowo near Witebsk (Vitebsk) is presented. It shows the Monastery's history as seen against religious conflicts between the followers of the Orthodox and Uniate Churches in the 17th cand 18th centuries, the conflicts particularly vivid in Witebsk where the memory of the assassination of Archbishop Jozafat Kuncewicz (1623) made the restitution of the Orthodox Church a sensitive issue. The Ogiñski family were the founders and benefactors of the Markowo Monastery in the 17th century. In harmony with the Eastern monastic tradition, the complex of buildings grouped around a courtyard created an almost self-sufficient separate town. It was composed of the following: two Orthodox churches: the wooden one of the Holy Trinity (after 1685-1690), richly furnished, and the brick one of the Intercession of the Theotokos (1754-1755), together with monastery buildings. Additionally, two wooden Orthodox churches belonged to the Monastery: the cemetery one of St Nicholas and of St Praxedes (both ca 1730).
Keywords: Geschichte 1600-1750; Klosteranlage; Witebsk; Markowo -- Mohrungen